Tenofovir diphosphate levels in dried blood spots are associated with virologic failure and resistance to first‐line therapy in South Africa: a case–control cohort study. Issue 12 (15th December 2021) - Castillo‐Mancilla, Jose R.; Edwards, Johnathan A.; Brijkumar, Jaysingh; Moosa, Mahomed‐Yunus; Zhao, Yuan; Ofotokun, Igho; Johnson, Brent A.; Lee, Mitchell H.; Pillay, Selvan; Pillay, Melendhran; Moodley, Pravi; Kuritzkes, Daniel R.; et al.
Abstract: Introduction: Tenofovir diphosphate (TFV‐DP) in dried blood spots (DBS), a measure of cumulative antiretroviral therapy (ART) adherence, is associated with viral suppression and predicts future viremia in persons with HIV (PWH). However, its utility to identify those at risk for virologic failure (VF) and drug resistance is unknown. To address this, we aimed to establish the association between this adherence biomarker and VF with drug resistance in a cohort of PWH initiating first‐line ART in KwaZulu‐Natal, South Africa. Methods: PWH initiating TFV disoproxil fumarate (TDF)‐based ART within a parent prospective cohort were evaluated. Using a nested design, DBS for TFV‐DP were collected from cases who developed VF (HIV‐1 RNA ≥1000 copies/ml) after ≥ 5 months on ART versus controls, matched 1:2 by site, age, gender, race and ART duration. Cases were categorized as having VF with or without resistance using genotyping. One‐way analysis of variance (ANOVA) was used to compare TFV‐DP for controls, cases with VF and resistance, and cases with VF without resistance. Data are presented as mean (standard deviation, SD) or geometric mean [95% confidence interval, 95% CI]. Results and discussion: One thousand participants were enrolled in the parent study between 2014 and 2016, of which 288 (29%) had DBS available. Of these, 94 (33%) were cases and 194 (67%) were controls; 59% were women. Mean age of our population was 33 (SD 8) years. Genotyping was available in 50 (53%) of the 94 cases. Geometric mean TFV‐DP in DBS from controls was 708 [95% CI; 647–773] fmol/punch, which was higher compared to participants having VF with resistance ( n = 36), 386 [95% CI; 241–617] fmol/punch and VF without resistance ( n = 14), 61 [95% CI; 22–164] fmol/punch; p <0.001. Genotype could not be obtained in 44 (47%) cases. Conclusions: TFV‐DP in DBS showed a stepwise association with VF and drug resistance in South African PWH. Participants having VF with resistance had mid‐range concentrations of TFV‐DP, which were higher than those for PWH without resistance. Future research on the clinical utility of TFV‐DP concentrations in DBS to predict and prevent the development of VF and drug resistance is needed.